2022
DOI: 10.1097/md.0000000000028798
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to take and ever use of pre-exposure prophylaxis among female sex workers in Ghana

Abstract: Pre-exposure prophylaxis (PrEP) is a drug taken by people who are human immunodeficiency virus (HIV) negative and at increased risk of acquiring HIV. It's an effective intervention for HIV prevention. This study seeks to report on the prevalence and determinants of willingness to take and ever use of PrEP among female sex workers (FSW) in Ghana.The data analyzed was obtained from the Integrated Bio-behavioral Surveillance Survey conducted across the 16 regions of Ghana in 2020. Analysis was only performed on F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…20 Contrary to our findings, results from other studies done in Brazil, Tanzania, central Uganda, Kenya, Ghana, and China, reported significantly lower prevalence rates of PrEP use among female sex workers, ranging from 1.4 to 11%. 16,[21][22][23][24][25] The difference in prevalence rates could be attributed to various factors, including differences in sample size, geographical location, cultural norms, access to healthcare services, and the promotion of PrEP initiatives in the diverse settings.…”
Section: Discussionmentioning
confidence: 99%
“…20 Contrary to our findings, results from other studies done in Brazil, Tanzania, central Uganda, Kenya, Ghana, and China, reported significantly lower prevalence rates of PrEP use among female sex workers, ranging from 1.4 to 11%. 16,[21][22][23][24][25] The difference in prevalence rates could be attributed to various factors, including differences in sample size, geographical location, cultural norms, access to healthcare services, and the promotion of PrEP initiatives in the diverse settings.…”
Section: Discussionmentioning
confidence: 99%
“…Among many interventional strategies to prevent the spread of HIV, administering preexposure prophylaxis (PrEP) has been identified as a practical way to reduce incidence. [20][21][22] PrEP can be presented as a daily medication to prevent a diagnosed HIV-negative person from getting infected. 23 PrEP is the use of antiretrovirals in individuals who do not have HIV to prevent infection.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 The uptake of antiretrovirals as an effective means of preventing the spread of HIV is reported to be globally low. 20,[39][40][41] Many other barriers to PrEP implementation and antiretroviral usage are seen in the stigma surrounding its use among individuals at increased risk of HIV, the possible drug-to-drug interaction, the risk of sexually transmitted infection, the cost of antiretrovirals, and its reported side effects. [41][42][43] Additionally, the cost of antiretrovirals has been shown to significantly affect PrEP implementation among key Ghanaian population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This proactive step paved the way for the commencement of PrEP services to key populations a year later, in August 2020, with a particular emphasis on MSM (13). Research conducted in Ghana before the rollout of PrEP consistently indicated that a lack of awareness and knowledge among Ghanaian MSM was a significant barrier to PrEP's acceptance (14,15).…”
Section: Introductionmentioning
confidence: 99%